Body composition of goalkeepers from the basic categories of top football from Minas Gerais - Berto, Elano Silva de Magalhães (2014)
Purpose: Compare and describe the fat percentage (%F) of athletes that practice football as goalkeepers from the basic categories of Minas’ top football, according to age and the clubs that they represent. Materials and Methods: The sample was composed of 36 males, divided into categories: U-14 (n=9), U-15 (n=9), U-17 (n=9) and U-20 (n=9). Anthropometric evaluations were carried out in order to obtain the age, weight, BMI, height and %F, with the latter being the main purpose of the study. The ttest was used to compare the difference between goalkeepers’ %F averages. The significance level of p≤ 0,05 was adapted for interpretation matters. Results: The goalkeepers didn’t show a statistically significant difference when compared by categories. Discussion: For accomplishing a good performance in the sports practice, like football, it is important for the young athletes to have a great physical development. Conclusion: The physical preparation in team sports of a high level is planned according to the tactic role of the athlete. For the goalkeeper position, the %F is not as strict as for the other field positions. However, it is necessary to be able to carry out the tasks in the field accurately. There is a preference in selecting athletes with lower%F. In the assessed clubs, this characteristic was homogeneous.